Bisphenol A exposure induces gut microbiota dysbiosis and consequent activation of gut-liver axis leading to hepatic steatosis in CD-1 mice. (October 2020) - Feng, Dan; Zhang, Hongmin; Jiang, Xin; Zou, Jun; Li, Qingrong; Mai, Haiyan; Su, Dongfang; Ling, Wenhua; Feng, Xiang
Abstract: Interactions between the intestine and the liver, the so-called 'gut-liver axis', play a crucial role in the onset of hepatic steatosis and non-alcoholic fatty liver disease. However, not much is known about the impact of environmental pollutants on the gut-liver axis and consequent hepatic steatosis. Bisphenol A (BPA), a widely used plasticiser, is an important environmental contaminant that affects gut microbiota. We hypothesised that BPA induces hepatic steatosis by promoting gut microbiota dysbiosis and activating the gut-liver axis. In this study, male CD-1 mice were fed with diet containing BPA (50 μg/kg body weight/day) for 24 weeks. Dietary exposure to BPA increased lipid contents and fat accumulation in the liver. Analysis of 16 S rRNA gene sequencing revealed that the diversity of gut microbiota reduced and the composition of gut microbiota was altered in the BPA-fed mice. Further, the abundance of Proteobacteria, a marker of dysbacteria, increased, whereas the abundance of Akkermansia, a gut microbe associated with increased gut barrier function and reduced inflammation, markedly decreased. Expression levels of intestinal tight junction proteins (zona occludens-1 and occludin) also decreased drastically, leading to increased intestinal permeability and elevated levels of endotoxins. Furthermore, BPA up-regulated the expression of Toll-like receptor 4 (TLR4) and phosphorylation of nuclear factor-kappa B (NF-κB) in the liver and increased the production of inflammatory cytokines, including interleukin-1β, interleukin-18, tumour necrosis factor-α, and interleukin-6. Take together, our work indicated that dietary intake of BPA induced hepatic steatosis, and this was closely related to dysbiosis of gut microbiota, elevated endotoxin levels, and increased liver inflammation through the TLR4/NF-κB pathway. Graphical abstract: Image 1 Highlights: Dietary exposure to environmentally relevant doses of BPA induced hepatic steatosis. BPA exposure induced gut microbiota dysbiosis and reduced gut barrier function. BPA increased LPS levels and activated liver inflammation through TLR4/NF-κB pathway. BPA-induced hepatic steatosis was related to the activation of gut-liver axis. Abstract : Main finding of this work : BPA-exposure induced dysbiosis of the gut microbiota and reduced the intestinal barrier function, which led to increased levels of endotoxins and liver inflammation through the TLR4/NF-κB pathway, leading to hepatic steatosis.